Transforming Healthcare through AI: Unleashing the Power of Personalized Medicine - khan, Abdullah (International Journal of Multidisciplinary Sciences and Arts, 2023)
The healthcare sector now places a lot of emphasis on providing patients with personalized care that is catered to their unique requirements and features. A significant force behind the development and use of customized healthcare is artificial intelligence (AI). This essay examines the use of AI in personalized healthcare and how it can affect several facets of healthcare provision. The study starts out by talking about how AI is being used in diagnostics, emphasizing how machine learning algorithms and the examination of various datasets can improve diagnostic accuracy. It goes into more detail about how AI can be used to create tailored treatment plans, utilizing patient-specific data and predictive analytics to maximize therapeutic results and reduce side effects. Examined are the ethical issues surrounding AI in customized healthcare, such as data privacy, algorithmic bias, and the value of responsibility and openness. The integration of AI into clinical practice is also covered in the study, along with prospects for improving decision-making, streamlining workflow, and overall healthcare delivery effectiveness. The healthcare sector now places a lot of emphasis on providing patients with personalized care that is catered to their unique requirements and features. A significant force behind the development and use of customized healthcare is artificial intelligence (AI). This essay examines the use of AI in personalized healthcare and how it can affect several facets of healthcare provision. The study starts out by talking about how AI is being used in diagnostics, emphasizing how machine learning algorithms and the examination of various datasets can improve diagnostic accuracy. It goes into more detail about how AI can be used to create tailored treatment plans, utilizing patient-specific data and predictive analytics to maximize therapeutic results and reduce side effects. Examined are the ethical issues surrounding AI in customized healthcare, such as data privacy, algorithmic bias, and the value of responsibility and openness. The integration of AI into clinical practice is also covered in the study, along with prospects for improving decision-making, streamlining workflow, and overall healthcare delivery effectiveness.